Efficacy of SMART Stent Placement for Salvage Angioplasty in Hemodialysis Patients with Recurrent Vascular Access Stenosis - Shingo Hatakeyama; Terumasa Toikawa; Akiko Okamoto; Hayato Yamamoto; Kengo Imanishi; Teppei Okamoto; Noriko Tokui; Yuichiro Suzuki; Naoki Sugiyama; Atsushi Imai; Yasuhiro Hashimoto; Shigemasa Kudo; et al. (International Journal of Nephrology)
Vascular access stenosis is a major complication in hemodialysis patients. We prospectively observed 50 patients in whom 50 nitinol shape-memory alloy-recoverable technology (SMART) stents were used as salvage therapy for recurrent peripheral venous stenosis. Twenty-five stents each were deployed in native arteriovenous fistula (AVF) and synthetic arteriovenous polyurethane graft (AVG) cases. Vascular access patency rates were calculated by Kaplan-Meier analysis. The primary patency rates in AVF versus AVG at 3, 6, and 12 months were 80.3% versus 75.6%, 64.9% versus 28.3%, and 32.3% versus 18.9%, respectively. The secondary patency rates in AVF versus AVG at 3, 6, and 12 months were 88.5% versus 75.5%, 82.6% versus 61.8%, and 74.4% versus 61.8%, respectively. Although there were no statistically significant difference in patency between AVF and AVG, AVG showed poor tendency in primary and secondary patency. The usefulness of SMART stents was limited in a short period of time in hemodialysis patients with recurrent vascular access stenosis.